Sustainable phosphorus management in cover cropping systems to improve water quality - Sakib, Tamjid Us (My University, 2025)
Phosphorus (P) loading in agricultural runoff is a major contributor to surface-water impairment and harmful algal blooms. To develop strategies that both sustain crop production and protect water quality, we conducted a long-term study (2019-2025) at the Kansas Agricultural Watershed field laboratory near Manhattan, KS, evaluating the combined effects of cover crops and P management on runoff, sediment loss, and different forms of P loss in a no-till corn-soybean rotation. The experiment used a 3 x 2 factorial design with three P fertilizer treatments Control, Build and Maintain, (2019-2025) and Drawdown, (2019-2022) or Sufficiency (2022-2025) and two cover crop treatments (with or without cereal rye) applied to 18 bermed and terraced 0.5-ha watersheds arranged in a randomized complete block design with three replications. Each watershed was instrumented with 45-cm H Flumes and automated samplers to monitor runoff and collect flow-weighted composite samples for water-quality analyses. For interpretation, 2020-2022 and 2023-2025 represent the drawdown and sufficiency phases, respectively. During the drawdown phase, cover crops significantly reduced runoff during years with intense storms, consistently decreased soil erosion by 70-90%, and lowered particulate P losses by 36-73%, demonstrating strong erosion-control benefits. However, cover crops introduced a tradeoff by increasing dissolved reactive P losses by one- to two-fold, particularly under build and maintain P management where soil test P remained high. In contrast, drawdown management of legacy P reduced all forms of P loss across years, with significant total P reductions emerging after only one year, highlighting an immediate benefit. Integrating cover crops with drawdown minimized dissolved reactive P losses to levels comparable to build and maintain P management without cover crops, and cover crop-related P loss was consistently higher under build and maintain than under drawdown management. These results highlight the value of pairing cover crops with P drawdown management strategies to reduce P loss and improve water quality in no-till systems with legacy P, where crops can rely on drawing down existing P reserves without additional fertilizer. Over the sufficiency phase, cover crops combined with either build and maintain or sufficiency management reduced runoff compared with no cover treatments, with no significant differences between build and maintain management and sufficiency in runoff reduction. Cover crops cut sediment loss by 60-80% and reduced particulate P losses by up to 72%, again underscoring the erosion-control benefits of cover crops. Dissolved reactive P losses were consistently lower under sufficiency than build and maintain management and cover crops did not raise dissolved reactive P under sufficiency except during the wetter year (2024). Total P losses varied over the years, increasing in 2024 but declining in 2025. Cover crops and SF management reduced corn yields by 10% only in 2023, with no treatment effects observed in 2024 and 2025. Taken together, these results show that cover crops reliably reduce runoff, soil erosion, and particulate P loss under both short-term drawdown and sustainable sufficiency management but may increase dissolved reactive P loss when soil P is high. Therefore, integrating cover crops with drawdown or sufficiency strategies should be guided by site-specific soil test P using drawdown until crop response emerges, followed by sufficiency management. This approach provides a balanced strategy to sustain yields, minimize legacy P buildup, and protect downstream water quality in no-till corn-soybean systems. To understand the potential mechanisms of driving increased dissolved reactive P loss with cover crops, a greenhouse study was also conducted. Since Plant species can modify the P sorption in soils through the release of low molecular weight organic acids (LMWOAs) in their root exudates. These LMWOAs compete with P for adsorption sites on soil minerals and induce dissolution of Fe and Al oxyhydroxides via complexation or ligand promoted dissolution, which could affect P availability for crops and P loss. This study examined the effect of plant species and P input on the P sorption dynamics with respect to LMWOA. A greenhouse study was conducted with ten different plant species, two P fertilizer treatments (0 and 70 kg P ha⁻¹), and two-time intervals (35 and 70 days). All treatments were structured in a 10 x 2 x 2 complete factorial with two controls arranged in a randomized complete block design with five replicates (210 experimental units). Species from Poaceae and Fabaceae exhibited a consistent trend of increased LMWOA release in low P compared to high P conditions whereas Brassicaceae species consistently released higher concentrations of LMWOAs regardless of P. On average, LMWOA release followed the order: Brassicaceae > Fabaceae > Poaceae. In certain circumstances, P availability may be more closely related to specific LMWOAs, particularly oxalic and citric acids, rather than total LMWOA concentration. Their influence on P sorption and water-extractable P is dependent on plant species, growth stage and P status. Our findings suggest that certain cover crop species rye, triticale and crimson clover may have potential to enhance P availability as well as minimize P loss.
Keywords: Phosphorus loss; Water quality; Cover crop; Root Exudates; Phosphorus management; Crop species